New and unusual host records for North American and South American spider wasps (Hymenoptera: Pompilidae) - Kurczewski, Frank E.; West, Rick C.; Waichert, Cecilia; Kissane, Kelly C.; Ubick, Darrell; Pitts, James P. (Zootaxa, 2020)
New and unusual host records for 133 species and subspecies of Pompilidae predominantly from the southwestern United States, Mexico, Central America, and South America are presented in modified taxonomic order. First-time species host records are given for Calopompilus Ashmead, Pepsis Fabricius, Hemipepsis Dahlbom, Priocnessus Banks, Entypus Dahlbom, Pompilocalus Roig-Alsina, Sphictostethus Kohl, Auplopus Spinola, Ageniella Banks, Eragenia Banks, Aporus Spinola, Poecilopompilus Ashmead, Tachypompilus Ashmead, Anoplius Dufour, Priochilus (Fabricius) and Notocyphus Smith. New host spider families are introduced for Calopompilus, Pepsis, Hemipepsis, Priocnessus, Entypus, Cryptocheilus Panzer, Priocnemis Schiødte, Auplopus, Ageniella, Eragenia, Aporus, Tachypompilus, Anoplius, Priochilus and Notocyphus. Eight host spider families are reported from the Western Hemisphere for the first time: Halonoproctidae (Notocyphus dorsalis dorsalis Cresson); Dipluridae (Pepsis pretiosa Dahlbom, P. montezuma Smith, P. infuscate Spinola, P. atripennis Fabricius, P. martini Vardy, Priocnessus vancei Waichert and Pitts); Nemesiidae (Pepsis pallidolimbata Lucas, P. viridis Lepeletier, P. spp., Pompilocalus hirticeps (Guérin), Sphictostethus gravesii (Haliday), S. striatulus Roig-Alsina, Priocnemis oregona Banks); Barychelidae (Eragenia sp.); Paratropididae (Pepsis stella Montet); Trechaleidae (Hemipepsis toussainti (Banks), Entypus unifasciatus cressoni (Banks), Tachypompilus ferrugineus (Say), Tachypompilus unicolor cerinus Evans, Priochilus gloriosum (Cresson); Desidae (Ageniella accepta (Cresson), Sphictostethus isodontus Roig-Alsina) and Selenopidae (Priochilus scrupulum (Fox), Tachypompilus erubescens (Taschenberg) or xanthopterus (Rohwer)). The first known host records for the rare South American pompilid genera Chirodamus (Lycosidae: Lycosa sp.) and Herbstellus (Nemesiidae: Diplothelopsis cf bonariensis Mello-Leitão) are presented.